A general method for selectively coating photothermal materials on 3D porous substrate surfaces towards cost-effective and highly efficient solar steam generation. Issue 46 (17th November 2020) - Shao, Bo; Wu, Xuan; Wang, Yida; Gao, Ting; Liu, Zhao-Qing; Owens, Gary; Xu, Haolan
Abstract : An interfacial gelation coating method is developed to selectively coat photothermal materials on 3D substrate surfaces which dramatically reduces the consumption of photothermal materials while delivering superior performance in solar evaporation. Abstract : Photothermal materials (PTMs) based solar steam generation is one of the most promising technologies to mitigate global clean water shortages. Compared to 2D photothermal evaporators, recently developed 3D counterparts can dramatically improve the evaporation rate and energy efficiency of solar evaporation. However, 3D evaporators require much more PTMs which significantly increases the cost of evaporator fabrication. During solar steam generation, since light absorption and solar evaporation only take place on the evaporator surface, in principle only the surfaces of the 3D porous substrates need to be coated with PTMs, but this is currently very challenging. In this work, a general interfacial gelation method is developed to enable the selective coating of various PTMs on the surfaces of 3D porous substrates. With the same PTMs consumption, the evaporation rates of the 3D photothermal evaporators fabricated by this selective surface coating method are increased to 165.7–185.3% compared to that of the evaporators prepared by a traditional coating method. In addition, to achieve the same evaporation rate, the selective surface coating only requires <25% of PTMs. This surface coating method thus paves the way for large-scale application of 3D photothermal evaporators for clean water production by solar evaporation.